SIRT2 controls the pentose phosphate switch. (13th May 2014) - Wu, Lindsay E; Sinclair, David A
<x xml:space="preserve">Abstract</x> The most common enzyme defect in humans is glucose‐6‐phosphate dehydrogenase (G6PD) deficiency, which affects more than 400 million people. G6PD shunts glucose into the pentose phosphate pathway (PPP) to generate nucleotides and reducing potential in the form of NADPH. In this issue, Wang et al (2014) show that G6PD activity is post‐translationally regulated by SIRT2, a cytoplasmic NAD+‐dependent deacetylase, thereby linking NAD+ levels to DNA repair and oxidative defences, and identifying potential new approaches to treating this common genetic disease.